Everyday war : the conflict over Donbas, Ukraine - Uehling, Greta Lynn (Cornell University Press, 2023)
"This book explores what noncombatant civilians go through in a country at war. The first half takes place in the parts of Ukraine still controlled by central authorities, exploring friend, family, and romantic partner relationships to demonstrate how war can reconfigure intimacy. The second half is focused on life in and around the Donetsk and Luhansk provinces, where residents in close proximity to the military conflict were left, for the most part, to fend for themselves. A place with mercenary gunmen, criminal gangs, and political chaos was paradoxically also a place where ethics thrived"--